Symptoms of Uterine Dystemperament in Abnormal Uterine Bleeding from Perspective of Persian Medicine - Fatemeh Moradi; Fatemeh Alizadeh; Nafiseh Zafarghandi; Farhad Jafari; Mahdi Alizadeh Vaghasloo; Mehrdad Karimi (Tehran University of Medical Sciences, 2019)
Abnormal Uterine Bleeding (AUB) is the most common reason for women's medical referral in the reproductive age. In Persian Medicine, one of the major causes of this disorder is known as uterine dystemperament (Su-e Mizaj). AUB is known as "Kesrat-e Tams" in this medical school. We aimed to investigate the frequency of positive symptoms of uterine dystemperament in patients with AUB from the perspective of Persian Medicine. This cross-sectional study was conducted from October 2009 to September 2010 in Tehran, Iran. It comprised 70 patients with abnormal uterine bleeding who were 15-45 years old. Data were collected by a questionnaire prepared based on the textbooks of Persian Medicine. The frequency of each symptom of uterine dystemperament was obtained. Among the four uterine dystemperaments, the "dry" and "warm" uterine types had the highest rankings. In patients with excess uterine hemorrhage, the symptoms of warm uterine is more frequent than cold uterine. Meanwhile, the warm uterine dystemperament interference was also observed in excess uterine hemorrhage.